Vitamin D Deficiency and Distal Radius Fractures: A Case-Control Study: Vitamin D Deficiency and Distal Radius Fractures - Javaid, Junaid; Malik, Aqsa; Rauf, Faizan; Rehman, Muhammad; Amatulnaval, .; Noureen, Fakhara (Pakistan Journal of Health Sciences, 2026)
Deficiency of vitamin D is considered a significant risk factor for fragile fractures. It is highly prevalent in South Asia despite the fact that sunlight is abundant. In the literature, there is limited data available regarding any association between deficiency of vitamin D levels and distal radius fractures (DRFs) specifically for the Pakistani population. Objectives: To find out the prevalence and severity of deficiency of vitamin D in patients with DRFs and to determine the association of fracture type, severity, and mechanism of injury with vitamin D levels. Methods: It was a case–control study that was conducted at Naseer Memorial Hospital, Azad Kashmir, consisting of 216 cases and 100 controls. Vitamin D in serum was estimated using a chemiluminescent immunoassay (Abbott Architect i2000SR). DRFs were confirmed on radiography due to a standard PA and lateral view of the wrist using a GE Optima XR220amx digital X-ray system. The AO system was used to classify the fractures. Statistical analysis of the data was done in SPSS version 23.0, while p<0.05 was taken as significant. Results: Vitamin D deficiency was significantly higher among patient’s vs controls (p<0.001). Lower vitamin D levels correlated inversely with fracture severity (r = –0.47, p<0.01). Extra-articular fractures and low-energy trauma predominated. Female and elderly patients exhibited greater deficiency and more complex fractures. Conclusions: The deficiency of vitamin D is an important and independent predictor of DRFs specially in elderly female patients, and routine screening of vitamin D levels should be integrated into the fracture prevention strategy.